Potential Development of Integrated Transportation Policy in Borobudur Area, Magelang Regency - Ariadi Heri; Wibowo Dwi Edi; Prematura Aditya Migi; Aditya Agung (E3S Web of Conferences)
The Borobudur area is a popular tourist destination in Magelang Regency. The purpose of this study is to determine the potential design concept for integrated tourist transportation in the Borobudur area, Magelang Regency. This study was conducted from July to October 2022 in the Borobudur tourist area. The research method used was qualitative descriptive by data analysis sampling. The research findings indicate that the Borobudur region has the potential for progressive tourism growth in the sectors of natural and cultural tourism. As a strategic tourism area, Borobudur has 4 tourism development zones, namely natural and cultural tourism, natural tourism, volcanology tourism, and village tourism. Based on this potential and legal references, a master plan model for spatial planning guidelines for Magelang Regency can be created. According to survey data, the majority of tourists in the Borobudur area, in addition to visiting Borobudur Temple, tend to visit other attractions such as Punthuk Setumbu, Gereja Ayam, Mendut Temple, Mount Sumbing, Mangli Sky View, Telaga Bleder, Curug Silawe, Nepal Van Java, Ketep Pass, and Pawon Temple. From this information, the potential and threat retention regarding the implementation of integrated tourism area development will be identified, and policy proposals for tourism development will be presented. The conclusion of this study shows that the Borobudur Temple area has diverse tourism potentials that can be developed comprehensively by creating an integrated transportation system model, which will be outlined in a special regional regulation aimed at protecting the area.